Decreased Protein Quality Control Promotes the Cognitive Dysfunction Associated With Aging and Environmental Insults - Jin, Hisayo; Komita, Mari; Aoe, Tomohiko (Frontiers in Neuroscience, 2018)
Background: Most neurodegenerative diseases are sporadic and develop with age. Degenerative neural tissues often contain intra- and extracellular protein aggregates, suggesting that the proteostasis network that combats protein misfolding could be dysfunctional in the setting of neurodegenerative disease. Binding immunoglobulin protein (BiP) is an endoplasmic reticulum (ER) chaperone that is crucial for protein folding and modulating the adaptive response in early secretory pathways. The interaction between BiP and unfolded proteins is mediated by the substrate-binding domain and nucleotide-binding domain with ATPase activity. The interaction facilitates protein folding and maturation. BiP has a recovery motif at the carboxyl terminus. The aim of this study is to examine cognitive function in model mice with an impaired proteostasis network by expressing a mutant form of BiP lacking the recovery motif. We also investigated if impairments of cognitive function were exacerbated by exposure to environmental insults, such as inhaled anesthetics. Method: We examined cognitive function by performing radial maze testing with mutant BiP mice and assessed the additional impact of general anesthesia in the context of proteostasis dysfunction. Testing over 8 days was performed 10 weeks, 6 months, and 1 year after birth. Results: Age-related cognitive decline occurred in both forms of mice. The mutant BiP and anesthetic exposure promoted cognitive dysfunction prior to the senile period. After senescence, when mice were tested at 6 months of age and at 1 year old, there were no significant differences between the two genotypes in terms of the radial maze testing; furthermore, there was no significant difference when tested with and without anesthetic exposure. Conclusion: Our data suggest that aging was the predominant factor underlying the impairment of cognitive function in this study. Impairment of the proteostasis network may promote age-related neurodegeneration, and this is exacerbated by external insults.